2019
DOI: 10.1111/gfs.12430
|View full text |Cite
|
Sign up to set email alerts
|

Dry‐matter losses and changes in nutrient concentrations in grass and maize silages stored in bunker silos

Abstract: To reduce losses and improve forage use efficiency in dairy farming systems, mass and nutrient flows during silage production have to be measured from the field to feed bunk. However, data on these losses at the farm scale are scarce. Thus, we examined dry‐matter (DM) losses and changes in nutrient concentrations (proximate constituents, nitrogen [N], phosphorus [P]) and energy values (net energy for lactation [NEL]) of silages on three experimental farms from ensiling to feed‐out. The investigated material in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…There was a slight increase in the overall compositions of NDF, ADF, ADL, CL, and HC. Stable ADL and decreased fiber compositions, i.e., NDF, ADF, CL, and HC, were reported by Köhler et al (2019) and Dong et al (2020), who co-ensiled grass with maize and Broussonetia papyrifera with perennial ryegrass, respectively. The ADF content in this study was found to gradually decrease in the M5, M6, and M7 samples.…”
Section: Dynamic Changes In the Lignocellulosic Components During Ensilingmentioning
confidence: 74%
See 1 more Smart Citation
“…There was a slight increase in the overall compositions of NDF, ADF, ADL, CL, and HC. Stable ADL and decreased fiber compositions, i.e., NDF, ADF, CL, and HC, were reported by Köhler et al (2019) and Dong et al (2020), who co-ensiled grass with maize and Broussonetia papyrifera with perennial ryegrass, respectively. The ADF content in this study was found to gradually decrease in the M5, M6, and M7 samples.…”
Section: Dynamic Changes In the Lignocellulosic Components During Ensilingmentioning
confidence: 74%
“…The WSC content for all substrates decreased considerably in the first 10 d of ensiling due to microbial degradation. Afterwards, it fluctuated slightly until the end of the ensiling process, which could be due to the decomposition of starch and/or structural carbohydrates, i.e., hemicellulose and cellulose, by microbes and/or acids produced additional soluble carbohydrates to compensate for the consumed WSC (Köhler et al 2019).…”
Section: Dynamic Changes In the Nutrient Components During Ensilingmentioning
confidence: 99%
“…How-ever, Nguyen et al (2005) reported no difference in dry matter content of Orchard grass before and after ensiling. Similarly, Gerlach et al (2018) and Köhler et al (2019) also reported no difference in DM content of corn and grass silages. In the initial aerobic exchange stage, aerobic microorganisms continue to work with the remaining oxygen in the incubator.…”
Section: Dry Matter Content During Ensilingmentioning
confidence: 88%
“…Data in Table 8 shows that, NDF of CTL treatment was significant (P<0.05) difference between day 0 and day 21, whereas significant (P>0.05) differences were not showed in other treatments The result of NDF value was consistent with the hemicellulose content (by calculated the NDF-ADF content) of sunflower at 1.8% (Table 2). Some studies have reported that the silage often reduced the NDF content (Gerlach et al, 2018;Köhler et al, 2019), the result of the structural carbohydrates being hydrolysed by enzymes in the ensilage. However, Köhler et al (2019) showed that the decrease in NDF content was due to the reduction of hemicellulose, meaning that the ADF content did not decrease after incubation.…”
Section: Neutral Detergent Fibre Contentmentioning
confidence: 99%
See 1 more Smart Citation